2012
DOI: 10.2147/opth.s34639
|View full text |Cite
|
Sign up to set email alerts
|

Imaging late capsular bag distension syndrome: an anterior segment optical coherence tomography study

Abstract: BackgroundAnterior segment optical coherence tomography (ASOCT) was used to categorize and provide insights into the etiology of capsular bag distension syndrome (CBDS).MethodsA prospective review was undertaken of 10 cases who presented with signs of late CBDS 5–11 years after uneventful phacoemulsification with in-the-bag posterior chamber intraocular lens implantation.ResultsAll 10 patients presented with a milky collection within the distended capsular bag without raised intraocular pressure or a shallow a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…Limited research has been conducted on the changes of ACD in late CBS. Some studies 16,17 found small changes in ACD after laser treatment, as measured by anterior segment OCT. In our three cases, however, an increase in ACD after laser treatment was evident, ranging from 0.20 to 0.45 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Limited research has been conducted on the changes of ACD in late CBS. Some studies 16,17 found small changes in ACD after laser treatment, as measured by anterior segment OCT. In our three cases, however, an increase in ACD after laser treatment was evident, ranging from 0.20 to 0.45 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Nd:YAG posterior capsulotomy was performed in all the cases safely and yielded excellent visual results in all cases, with minimal biometric or refractive changes. Few reports demonstrated that in CBDS, distended capsular bag due to trapped milky fluid poses technical difficulty in focusing of the Nd:YAG laser on the posterior capsule, hence leading to failure, which may then require surgical drainage of the trapped fluid [15]. In all our cases, Nd:YAG laser assisted posterior capsulotomy was done in mid-periphery in the inferior part, as distension of bag leads to backward displacement of posterior capsule and therefore, center of posterior capsule cannot be visualized and focused.…”
Section: Discussionmentioning
confidence: 99%
“…It has been used in examination and analysis of the retina, 6,7 nerve fiber layer 8,9 , cornea, 10,11 and other structures in anterior segments. 10,11 In lens study, it has also been used to assess cataract 12 and PCO formation [13][14][15][16][17][18][19] in human eyes. Since OCT is an ideal tool to observe the structural changes of tissues longitudinally, it has been applied in contact lens edge fitting 20,21 and tear film assessment.…”
Section: Methodsmentioning
confidence: 99%